Transflip mutations produce deletions in pancreatic cancer. Issue 8 (29th May 2015) - Norris, Alexis L.; Kamiyama, Hirohiko; Makohon‐Moore, Alvin; Pallavajjala, Aparna; Morsberger, Laura A.; Lee, Kurt; Batista, Denise; Iacobuzio‐Donahue, Christine A.; Lin, Ming‐Tseh; Klein, Alison P.; Hruban, Ralph H.; Wheelan, Sarah J.; et al.
<x xml:space="preserve">Abstract</x> Pancreatic ductal adenocarcinoma (PDAC) is driven by the inactivation of the tumor suppressor genes (TSGs), CDKN2A (P16) and SMAD4 (DPC4), commonly by homozygous deletions (HDs). Using a combination of high density single‐nucleotide polymorphism (SNP) microarray and whole genome sequencing (WGS), we fine‐mapped novel breakpoints surrounding deletions of CDKN2A and SMAD4 and characterized them by their underlying structural variants (SVs). Only one third of CDKN2A and SMAD4 deletions (6 of 18) were simple interstitial deletions, rather, the majority of deletions were caused by complex rearrangements, specifically, a translocation on one side of the TSG in combination with an inversion on the other side. We designate these as "TransFlip" mutations. Characteristics of TransFlip mutations are: (1) a propensity to target the TSGs CDKN2A and SMAD4 (P < 0.005), (2) not present in the germline of the examined samples, (3) non‐recurrent breakpoints, (4) relatively small (47 bp to 3.4 kb) inversions, (5) inversions can be either telomeric or centromeric to the TSG, and (6) non‐reciprocal, and non‐recurrent translocations. TransFlip mutations are novel complex genomic rearrangements with unique breakpoint signatures in pancreatic cancer. We hypothesize that they are a common but poorly understood mechanism of TSG inactivation in human cancer. © 2015 Wiley Periodicals, Inc.